The Influence of Smartphone Use on the Cognitive Abilities and Emotional Intelligence of Students at Pogung 2 State Elementary School - Qois Syauqi Rabbani; Panji Hidayat; Ega Asnatasia Maharani; Satrianawati Satrianawati (Journal of Computers for Science and Mathematics Learning, 2025)
Smartphones have revolutionized communication and interaction, becoming essential, particularly for children and teens. However, there is a contradiction in their use among students. While smartphones hold significant potential as educational tools, the government has banned their use in elementary schools to safeguard children from potential negative effects. This study aims to analyze the impact of smartphone use on the cognitive abilities and emotional intelligence of students at Pogung 2 State Elementary School (SDN 2 Pogung). The research method employed is descriptive qualitative, focusing on 4th, 5th, and 6th-grade students. The research subjects were selected using purposive sampling, ensuring that the participants were representative of the target population in terms of smartphone usage habits and academic performance. Data were collected through observations, interviews, and questionnaires to measure the intensity of smartphone use and its relationship with students’ cognitive abilities and emotional intelligence. The results of the study indicate that smartphone use among students ranges from 1 to 3 hours per day. However, this intensity of use does not show a significant impact on students’ cognitive abilities or emotional intelligence. The primary factors influencing cognitive abilities and emotional intelligence are more determined by parental guidance, educators, and the students’ surrounding environment. The conclusion of this study is that smartphone use does not have a direct impact on students’ cognitive abilities and emotional intelligence. Therefore, it is recommended that further research be conducted to develop appropriate regulations regarding smartphone use for elementary school students, in order to maximize benefits and minimize potential negative impacts.